PJMHS 2021
DOI: 10.53350/pjmhs211592379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cuffed vs. Uncuffed Endotracheal Intubation efficacy in Cleft Palate Surgery procedure in children

Abstract: Background: From several decades, in case of pediatric oral surgeries, Uncuffed endotracheal tubes are preferred due to insufficient availability of evidences, Aim: To compare morbidity post-operatively after using uncuffed and cuffed endotracheal tubes in case of children undergoing surgery of cleft lip-palate. Methods: This study was carried out on children aging from 3 to 10 years. About 40 candidates participated and divided into two groups according to the list generated via computer. The comparison was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…At the same time, we found two studies on extubation position and bloodletting acupuncture interesting, both of which showed that extubation in the lateral position may reduce the probability of postoperative dyspnea (3,4,8).…”
Section: Introductionmentioning
confidence: 93%
“…At the same time, we found two studies on extubation position and bloodletting acupuncture interesting, both of which showed that extubation in the lateral position may reduce the probability of postoperative dyspnea (3,4,8).…”
Section: Introductionmentioning
confidence: 93%